2005
DOI: 10.1029/2004gb002341
|View full text |Cite
|
Sign up to set email alerts
|

Modeling impacts of farming management alternatives on CO2, CH4, and N2O emissions: A case study for water management of rice agriculture of China

Abstract: [1] Since the early 1980s, water management of rice paddies in China has changed substantially, with midseason drainage gradually replacing continuous flooding. This has provided an opportunity to estimate how a management alternative impacts greenhouse gas emissions at a large regional scale. We integrated a process-based model, DNDC, with a GIS database of paddy area, soil properties, and management factors. We simulated soil carbon sequestration (or net CO 2 emission) and CH 4 and N 2 O emissions from China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 27 publications
6
106
0
1
Order By: Relevance
“…Li et al (2005) ) were well correlated (n ¼ 9, r 2 ¼ 0.93, p < 0.01), but the estimation errors ranged from À220% to þ28.6%. Fumoto et al (2010) tested the DNDC-Rice model by using data from a paddy field in Japan; they found simulated seasonal N 2 O emissions of 0.08 to 0.65 kg N ha…”
Section: Nitrous Oxide Fluxesmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (2005) ) were well correlated (n ¼ 9, r 2 ¼ 0.93, p < 0.01), but the estimation errors ranged from À220% to þ28.6%. Fumoto et al (2010) tested the DNDC-Rice model by using data from a paddy field in Japan; they found simulated seasonal N 2 O emissions of 0.08 to 0.65 kg N ha…”
Section: Nitrous Oxide Fluxesmentioning
confidence: 99%
“…Simulation of N 2 O fluxes by using the DNDC model or the DNDC-Rice model has been reported by Li et al (2005), Babu et al (2006), and Fumoto et al (2010). Li et al (2005) reported that the DNDC model was capable of estimating the seasonal magnitudes of N 2 O fluxes from paddy sites, although discrepancies existed for about 20% of their tested cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The geographical distribution of the emissions is assessed by global (USEPA, 2006(USEPA, , 2012EDGARv4.2FT2010, 2013 and regional Chen et al, 2013;Chen and Prinn, 2006;Yan et al, 2009;Castelán-Ortega et al, 2014; inventories or by land surface models (Spahni et al, 2011;Zhang and Chen, 2014;Ren et al, 2011;Tian et al, 2010Tian et al, , 2011Li et al, 2005;Pathak et al, 2005). The emissions show a seasonal cycle, peaking in the summer months in the extratropics associated with the monsoon and land management.…”
Section: Rice Cultivationmentioning
confidence: 99%
“…This Tier 1 estimate of CH4 emissions was then compared to a Tier 3 estimate generated using the DeNitrification-DeComposition (DNDC) model, which was modified for paddy-rice through the addition of anaerobic soil biogeochemical processes (Li et al 2004(Li et al , 2005. Due to the passage of the Rice Straw Burning Act of 1991, the burning of rice residue in California has been gradually phased out (Hill et al 2006).…”
Section: Ch 4 Emissions From Livestock and Rice Cultivationmentioning
confidence: 99%